Reliability theory and practice - Bazovsky, Igor (Dover Publications, 2004)
Written by a pioneer in the development of reliability methods, this text applies statistical mathematics to the analysis of electrical, mechanical, and other systems employed in airborne, missile, and ground equipment. Geared toward upper-level undergraduate and graduate students, it is also a valuable reference for professionals. 1961 edition.